MONITORING PARASIT PADA BUDIDAYA IKAN DAN UDANG DI DAERAH ISTIMEWA YOGYAKARTA - Triyanto Triyanto; Alim Isnansetyo (Jurnal Perikanan Universitas Gadjah Mada, 2004)
Parasites often cause the great loss in aquaculture either in fish or shrimp aquacultures. The loss will become more serious when fish or shrimp are secondary infected especially by bacteria. The objective of this study was to identify parasites in fish and shrimp culture inYogyakartaSpecialProvince (DIY). Samples of fish and shrimp were collected from several aquaculture centers in this region including several fish and shrimp hatcheries. Observation of parasites was conducted microscopically and macroscopically.Results showed that giant tiger prawn (Penaeus monodon) cultured in DIY was often infected by Zoothamnium sp. and Gregarines sp.. In addition, giant freshwater prawn (Machrobrachium rosenbergii) was often infected by Apiosoma sp., Dactylogyrus sp., Epystilis sp., Glossatella piscicola, Gregarines sp. and Zoothamnium sp.. Moreover Apiosoma sp.,  Dactylogyrus sp., Gyrodactylus sp., Ichthyopthirius sp., and Trichodina sp. were found in nile (Oreochromis niloticus) culture. Similar parasites such as Apiosoma sp., Dactylogyrus sp., Henneguya sp. Ichtyoptirius sp. and Trichodina sp..were found in Osphronemus gaurami. Ichtyoptirius sp. and Trichodina sp. also were found in walking catfish (Clarias gariephinus).